2022
DOI: 10.1093/ndt/gfac263
|View full text |Cite
|
Sign up to set email alerts
|

Hippocampal subfield morphology in regular hemodialysis patients

Abstract: Background Hippocampal alterations have been implicated in the pathophysiology of cognitive impairment in hemodialysis patients. The hippocampus consists of several distinct subfields, and the molecular mechanisms underlying cognition might be associated with specific hippocampal subfield volume changes. However, this has not yet been investigated in hemodialysis patients. This study aimed to explore volumetric abnormalities in hippocampal subfields in regular hemodialysis patients. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 42 publications
0
2
0
Order By: Relevance
“…On the other hand, it has been shown that cerebral atrophy progresses rapidly in patients with CKD, especially in dialysis patients [ 12 , 13 , 14 , 15 , 16 , 17 ]. Brain atrophy is significantly associated with CI, and atrophy of the frontal lobe and hippocampus is more remarkable in such patients [ 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, it has been shown that cerebral atrophy progresses rapidly in patients with CKD, especially in dialysis patients [ 12 , 13 , 14 , 15 , 16 , 17 ]. Brain atrophy is significantly associated with CI, and atrophy of the frontal lobe and hippocampus is more remarkable in such patients [ 13 , 18 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…CKD results in the accumulation of both salt and water in the body and might be a risk factor correlated with AD onset and cognitive impairment [ 15 ]. A recent study identified that smaller hippocampal volumes in hemodialysis patients were associated with impaired cognition [ 16 ]. In addition, a recent Mendelian randomization study revealed that CKD alters the brain cortical structure, including a reduction in cortical thickness, indicating neurodegeneration due to kidney damage [ 17 ].…”
Section: Introductionmentioning
confidence: 99%